Sistem Pendukung Keputusan Penentuan Mekanik Terbaik Menerapkan Metode Simple Additive Weighting (SAW) - Frieyadie; Irfan Nainggolan; Asrani, Dwika (ADA Research Center, 2024)
PT.Arista Auto Lestari Ringrood Branch is an automotive company located in Medan City. Currently, the increasing number of mechanics employed by automotive companies makes the diversity of mechanics increasingly complex, making it difficult to choose the best mechanic. Therefore, it is necessary to develop a decision support system as an alternative solution, so that it can increase efficiency and effectiveness in selection and improve quality in determining the best mechanic. The decision support system for determining the best mechanic uses the SAW (simple additive weighting) method based on predetermined criteria and weights. The criteria used as indicators are Discipline, Initiative, Achievement, Cooperation, Order, Performance and social. The SAW (simple additive weighting) method was chosen because it is able to select the best alternative from a number of alternatives. This research was carried out by looking for the weight of each attribute, then ranking was carried out to determine the best mechanic. The results of this research are in the form of a decision support application, which can recommend the best mechanic at PT Arista Auto Lestari Ringrood Branch.